Is BRAF a prognostic factor in stage III skin melanoma? A retrospective study of 72 patients after positive sentinel lymph node dissection. (1st July 2014) - Picard, M.; Pham Dang, N.; D'Incan, M.; Mansard, S.; Dechelotte, P.; Pereira, B.; Mondie, J.M.; Barthelemy, I.
Summary: Background: BRAF was identified as an oncogene in skin melanoma in 2002, and since 2011 has been a therapeutic target in the treatment of metastatic melanoma. The role of BRAF mutation in tumour initiation and the disease course remains to be elucidated. Objectives: The main objective of our study was to determine whether there is a relationship between BRAF status and overall survival in patients with a melanoma and a positive sentinel lymph node. We also sought an association between BRAF status and the clinicopathological features of the melanoma. Finally, we looked for a potential heterogeneity of BRAF status in primary and metastatic tumours. Methods: All patients ( n = 72) treated for melanoma and with a positive sentinel lymph node at the University Hospital of Clermont‐Ferrand, France, between January 2000 and January 2010 were enrolled in the study. We investigated BRAF status in primary melanoma and lymph node metastatic tissue in our molecular pathology laboratory and collected the clinical and survival data. Results: Of the 72 patients, 32 had at least one BRAF mutation. There was a statistically significant difference in overall survival between the BRAF‐mutated and wild‐type populations. The only clinical feature related to BRAF status was metastatic burden. Of the 25 patients in whom we obtained the status in both locations, five had a discordant result. Conclusions: BRAF mutation is an indicator of poor prognosis in patients with stage III melanoma with a positive sentinel lymph node. BRAF status could be used in the staging of this population. BRAF has a role not only in cellular immortalization but also in metastatic spread.